An Analysis of the constitutional principles of equality and affirmative action vis-à-vis employment in Malaysia - Noor Shuhadawati Mohamad Amin,; Nor Hafizah Mohd Badrol Afandi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia's diverse and multicultural society poses unique challenges in achieving a balanced and inclusive employment landscape that upholds both the rights and needs of individuals. In this regard, constitutional principles of equality serve as the cornerstone for promoting non-discrimination in employment across the public and private sectors. The concept of equality embedded in the constitution today, on the other hand, is anchored in a complicated historical context that has greatly shaped the nation’s path. Hence, guaranteeing the effective application of the principle while taking into account the individual rights and needs of every community remains a difficult challenge. This is because affirmative action policy is also embedded in the constitution that aims at protecting the Bumiputera. Hence, understanding the historical context behind the establishment of the constitution is of utmost importance as it allows Malaysians to appreciate its unique features that seek to strike a delicate balance between the rights and needs of the people. This study which is doctrinal in nature, attempts to examine Malaysia's constitutional equality principles, with a special emphasis on understanding how to strike a balance between individual's rights and needs in the context of employment. This study tries to uncover the issues and challenges that impede the equitable implementation of the equality principle in the employment sector by evaluating historical events, existing legal frameworks, policies, and practices.